Incorporating User Participation in Heritage Institutions: Approaching Institutional Strategies in Relation to New Social Media and Audience Needs - Mancini, Federica (Journal of New Media and Mass Communication, 2015)
The gradual inclusion of the participation of the public in museums through social networks and other tools that enhance the user's leadership in the management of information and in the knowledge production seems to have led to an evolution in the cultural experience of the public. However, we do not know yet whether the possibility to intervene and manipulate the content really optimize the communication between visitors widening their possibilities of action turning them into a concerned and active audience. In this study, we have analyzed practices and motivations of on line audience, detecting some guidelines that should be considered when incorporating user participation in heritage institutions. The analysis of when a participatory environment can encourage the dissemination of the contents of the museum and engage audiences in an ongoing and repeated relationship that encompasses even the attendance realm, was performed using a qualitative methodological perspective though supported by some quantitative data related to the profiles of the recipients of cultural activities and their practices in the network. The suggestions proposed, by virtue of being the result of an evaluation process of public preferences, would highlight the real needs of on line visitors and reduce the dissociation between the way that museums seek to use their pages and effective practices of their users. Looking at these results, this research (based on the analysis of four case studies) represents an attempt to approach the strategies adopted by the institutional sphere in relation to the new social media and to the current needs of the public.